2020
DOI: 10.1002/anie.202014302
|View full text |Cite
|
Sign up to set email alerts
|

Gel‐Derived Amorphous Bismuth–Nickel Alloy Promotes Electrocatalytic Nitrogen Fixation via Optimizing Nitrogen Adsorption and Activation

Abstract: To achieve the electrochemical nitrogen reduction reaction (NRR) for efficient and sustainable NH3 production, catalysts should exhibit high selectivity and activity with optimal adsorption energy. Herein we developed a three‐dimensional (3D) amorphous BiNi alloy toward a significantly enhanced NRR compared with its crystalline and metal counterparts. Ni alloying enables the chemisorption of nitrogen and the lower free‐energy change for the *NNH formation, and the 3D alloy electrocatalyst exhibits high catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 50 publications
3
68
0
Order By: Relevance
“…Yu's group developed an amorphous BiNi alloy for the NRR, which was designed to activate N2 molecules by optimizing the adsorption energy and adjusting the crystallinity. 147 The BiNi alloy has a significantly smaller areaspecific impedance than Bi (Fig. 7c), indicating that the 3D nanoporous alloy framework promotes charge transport, thereby enhancing the NRR activity.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu's group developed an amorphous BiNi alloy for the NRR, which was designed to activate N2 molecules by optimizing the adsorption energy and adjusting the crystallinity. 147 The BiNi alloy has a significantly smaller areaspecific impedance than Bi (Fig. 7c), indicating that the 3D nanoporous alloy framework promotes charge transport, thereby enhancing the NRR activity.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
“…Copyright 2020, Wiley-VCH. 147 (d) Schematic illustration of a possible mechanism of RuFeCoNiCu NPs. Copyright 2020, Wiley-VCH.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
“…These two works indicate the significance of the electronic and geometric structure of the electrocatalysts in NRR. 248 Another highly desirable metal material for the electrochemical N 2to-NH 3 conversion is iron (Fe) given its important role as a catalyst system. 249 A typical example is its function as an earth-abundant and low-cost catalyst for NH 3 production in the industrial Haber-Bosch process.…”
Section: Metallic Substancementioning
confidence: 99%
“…Similarly, via in situ polymerization of crosslinked hydrogels, the contacts between LiFePO 4 cathode materials and PPy-based conductive hydrogels are enhanced, leading to significantly improved rate and cyclic performance of the composite electrode. 38 Hydrogels can be converted into various functional materials, such as carbons, 18,39 metals, 40 alloys 41 and metal oxides, 19 with the inherited hierarchical structures, large surface areas and bicontinuous mass/charge transport channels. Through the hydrogel-template approach, 3D interconnected nanoporous oxide frameworks can be constructed serving as an efficient and stable Li-ion electrolyte.…”
Section: Hydrogels For Energy Storagementioning
confidence: 99%
“…Alloy electrocatalysts with tunable composition and crystallinity can also be derived from hydrogels. To enhance the conductivity of Bi catalysts and modulate the adsorption energy, Fang et al 41 demonstrated a Bi-Ni alloy electrocatalyst derived from Bi-Ni inorganic hydrogels for NRR electrocatalysis. Inherited from hydrogel precursors, amorphic Bi-Ni alloys with disordered atom arrangement and defective surface provide plentiful active sites for nitrogen adsorption.…”
Section: Hydrogels For Electrocatalysismentioning
confidence: 99%